The Infection of Cucumber (Cucumis sativus L.) Roots by Meloidogyne incognita Alters the Expression of Actin-Depolymerizing Factor (ADF) Genes, Particularly in Association with Giant Cell Formation - Liu, Bin; Liu, Xingwang; Liu, Ying; Xue, Shudan; Cai, Yanling; Yang, Sen; Dong, Mingming; Zhang, Yaqi; Liu, Huiling; Zhao, Binyu; Qi, Changhong; Zhu, Ning; et al. (Frontiers in Plant Science, 2016)
Cucumber (Cucumis sativus L.) is threatened by substantial yield losses due to the south root-knot nematode (Meloidogyne incognita). However, understanding of the molecular mechanisms underlying the process of nematode infection is still limited. In this study, we found that M. incognita infection affected the structure of cells in cucumber roots and treatment of the cytoskeleton inhibitor (cytochalasin D) reduced root-knot nematode (RKN) parasitism. It is known that Actin-Depolymerizing Factor (ADF) affects cell structure, as well as the organization of the cytoskeleton. To address the hypothesis that nematode-induced abnormal cell structures and cytoskeletal rearrangements might be mediated by the ADF genes, we identified and characterized eight cucumber ADF (CsADF) genes. Phylogenetic analysis showed that the cucumber ADF gene family is grouped into four ancient subclasses. Expression analysis revealed that CsADF1, CsADF2-1, CsADF2-2, CsADF2-3 (Subclass I), and CsADF6 (Subclass III) have higher transcript levels than CsADF7-1, CsADF7-2 (Subclass II genes), and CsADF5 (Subclass IV) in roots. Members of subclass I genes (CsADF1, CsADF2-1, CsADF2-2, and CsADF2-3), with the exception of CsADF2-1, exhibited a induction of expression in roots 14 days after their inoculation (DAI) with nematodes. However, the expression of subclass II genes (CsADF7-1 and CsADF7-2) showed no significant change after inoculation. The transcript levels of CsADF6 (Subclass III) showed a specific induction at 21 DAI, while CsADF5 (Subclass IV) was weakly expressed in roots, but was strongly up-regulated as early as 7 DAI. In addition, treatment of roots with cytochalasin D caused an approximately 2-fold down-regulation of the CsADF genes in the treated plants. These results suggest that CsADF gene mediated actin dynamics are associated with structural changes in roots as a consequence of M. incognita infection.